Dėl lietuvių kalbos mišriųjų veiksmažodžių kamienų santykių ir darybos - Pakerys, Jurgis (Baltistica, 2002)
ON LITHUANIAN MIXED TYPE VERBS: STEM RELATIONS AND DERIVATION I have argued in this article that Lithuanian mixed type verbs are in fact suffixed verbs with alternating suffixal morphs which sometimes surface as zeroes (see Table l; cf. Andronov 1999, 73-75; 2000a, 42f). According to the morphemic structure of their stems all Lithuanian verbs split into two major classes of non suffixed vs. suffixed. The latter ones make up two subclasses depending on whether their main stems are parisyllabic or imparisyllabic (thematic vowels arc not counted). All imparisyllabic (traditional mixed type) verbs have alternating suffixes comparable to non automatic root vowel alternations and are employed in stem distinction, cf. praes. 3 reñka : inf. riñkti, praet. 3 riñko (‘gather’, e : i) and praes. 3 kal̃b-ø-a : inf. kalb-ė́-ti, praet. 3 kalb-ė́j-o (‘speak’, ø : ė; alternation ė → ėj /-V can be interpreted as automatic). These alternations are not independent distinctive features and mark verbal stems together with inflectional paradigms. Alternating verbal suffixes and root vowels are in complementary distribution: if a verb has a suffix it will not exhibit non automatic root vowel alternations (and vice versa). This distribution also affects present stem paradigms -n(-)a and -sta (e.g. praes. 3 ti-ñ-k-a ‘passes, matches’, gáu-n-a ‘gets’, tir̃p-st-a ‘melts’) which block root vowel alternations (inf. tìkti, gáuti, tir̃pti, praet. 3 tìko, gãvo, tir̃po) with some exceptions, e.g. inf. skrìsti, praes. skre-ñ-d-a, praet. skrìdo (‘fly’, i : e plus praes. stem characterised by -n-a).